THE IMPACT OF DIGITAL TECHNOLOGIES ON PSYCHOLOGICAL ADAPTATION AND SOCIAL INTEGRATION OF OLDER ADULTS: A COMPREHENSIVE ANALYSIS - Nadoyan, Anna; Stepanyan, Anahit (Modern Psychology, 2025)
In contemporary digital society the psychological well-being and social integration of older adults are increasingly connected to their attitudes toward digital technologies and their skills in using them. This study aims to analyze the psychological impact of digital technologies on individuals aged 65 and above, focusing on psychological adaptation, social health, and cognitive functions. The study was conducted in 2024-2025, involving 150 participants aged 65-85 years. Results indicate that active use of digital technologies can have both positive and negative psychological consequences, depending on the intensity of use, motivations, and level of social support. Key findings show that moderate use contributes to maintaining cognitive activity and strengthening social connections, while excessive or uncontrolled use can lead to stress, anxiety, and social isolation.